1998
DOI: 10.1111/j.1741-6248.1998.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Women Entrepreneurs in Romania, Poland, and the United States: Cultural and Family Influences on Strategy and Growth

Abstract: This study investigated the impact of culture and family on the strategies, opportunities, and barriers to growth for women entrepreneurs from Romania, Poland, and America. The purpose of this research was twofold: to gather information on women entrepreneurs cross‐culturally and to construct and integrate the perspective of the woman business owner in relation to the broader family and cultural context in which she is located. A design incorporating qualitative and quantitative measures was used to collect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 8 publications
(7 reference statements)
0
13
0
2
Order By: Relevance
“…The current study bridges this gap by including women-headed organizations self-classified as either family or non-family businesses in the rural parts of a country in transition to a market economy -Russia. Research in Central and Eastern Europe show current models of entrepreneurship, and new venture creation strategies may be transferable to these transitional economies if a holistic approach is used to facilitate learning and development (Gundry and Ben-Yoseph 1998). While Chrisman et al (2002) and suggest that the family may have a strong influence on perceptions and performance of the firms they own and manage, questions remain .…”
Section: Family Business Research In Transitional Economiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study bridges this gap by including women-headed organizations self-classified as either family or non-family businesses in the rural parts of a country in transition to a market economy -Russia. Research in Central and Eastern Europe show current models of entrepreneurship, and new venture creation strategies may be transferable to these transitional economies if a holistic approach is used to facilitate learning and development (Gundry and Ben-Yoseph 1998). While Chrisman et al (2002) and suggest that the family may have a strong influence on perceptions and performance of the firms they own and manage, questions remain .…”
Section: Family Business Research In Transitional Economiesmentioning
confidence: 99%
“…Research conducted within the transitional economies of Central and Eastern Europe has shown that models of entrepreneurship have high transferability to these cultures (Gibb 1993;Gundry and Ben-Yoseph 1998;Kickul et al 2010). Entrepreneurial firms are at the forefront of economic development in emerging economies (Neace 1999); as such, the influences on the growth and sustainability of these enterprises are of research and public policy interest.…”
Section: Introductionmentioning
confidence: 99%
“…Gundry and Ben-Yoseph (1998) find more similarities than differences across the cultures in Romania, Poland and the United States. When studying cultural and social influences of business systems, and when using culture as an argument for the study, it is necessary to include both differences and similarities.…”
Section: Culture In Family Business Studiesmentioning
confidence: 93%
“…These studies can be said to follow a colonial tradition in the sense that they mainly concern family firms in "exotic" transitional economies, i.e. countries in Asia or Eastern Europe (Gundry & Ben-Yoseph, 1998;Pistrui, Huang, Oksoy, Jing, & Welsch, 2001;Tan & Tong Fock, 2001).…”
Section: Culture In Family Business Studiesmentioning
confidence: 99%
“…Adicionalmente, verifica-se que os 34,25% restantes dividem-se em 16 temá-ticas, entre os quais se verificam estudos sobre criação de novos negócios (Au & Kwan, 2009;Chang, Memili, Chrisman, Kellermmans, & Chua, 2009;Morris, Allen, Kutko, & Brannon, 2010), aprendizagem (Hamilton, 2011;Zahra, 2012), cultura (Hall, Melin, & Nordqvist, 2001;Zahra, Hayton, &Salvato, 2004), empreendedorismo feminino (Hisrich & Fülöp, 1997;Gundry & Ben-Yoseph, 1998), famílias empreendedoras (Nordqvist & Melin, 2010;Uhlaner, Kellermanns, Eddleston, & Hoy, 2012), oportunidades (Randoy & Goel, 2003;Patel & Fiet, 2011), empreendedorismo corporativo (Kellermanns & Eddleston, 2006), empreendedorismo estratégico (Webb, Ketchen, & Ireland, 2010), empreendedorismo familiar , empreendedorismo internacional (Sciascia, Mazzola, Astrachan, & Pieper, 2012), governança (Brunninge & Nordqvist, 2004), liderança (Ng & Thorpe, 2010), minorias (Purvear et al, 2008), processo empreendedor (Shepherd & Haynie, 2009) e redes empreendedoras (Anderson, Jack, & Dodd, 2005). Destacam-se ainda os trabalhos seminais de Brockhaus (1994), Dyer e Handler (1994) e Hoy e Verser (1994).…”
Section: Temas De Pesquisa Sobre Empreendedorismo Em Empresas Familiaresunclassified